Ileoanal pouch-related fistulae: A systematic review with meta-analysis on incidence, treatment options and outcomes. Issue 3 (March 2023) - Pellino, Gianluca; Celentano, Valerio; Vinci, Danilo; Romano, Francesco Maria; Pedone, Agnese; Vigorita, Vincenzo; Signoriello, Giuseppe; Selvaggi, Francesco; Sciaudone, Guido
Abstract: Background: Ileoanal pouch related fistulae (PRF) are a complication of restorative proctocolectomy often requiring repeated surgical interventions and with a high risk of long-term recurrence and pouch failure. Aims: To assess the incidence of PRF and to report on the outcomes of available surgical treatments. Methods: A PRISMA-compliant systematic literature search for articles reporting on PRF in patients with inflammatory bowel diseases (IBD) or familial adenomatous polyposis (FAP) from 1985 to 2020. Results: 34 studies comprising 770 patients with PRF after ileal-pouch anal anastomosis (IPAA) were included. Incidence of PRF was 1.5-12%. In IBD patients Crohn's Disease (CD) was responsible for one every four pouch-vaginal fistulae (PVF) (OR 24.7; p=0.001). The overall fistula recurrence was 49.4%; procedure-specific recurrence was: repeat IPAA (OR 42.1; GRADE +); transvaginal repair (OR 52.3; GRADE ++) and transanal ileal pouch advancement flap (OR 56.9; GRADE ++). The overall failure rate was 19%: pouch excision (OR 0.20; GRADE ++); persistence of diverting stoma (OR 0.13; GRADE +) and persistent fistula (OR 0.18; GRADE +). Conclusion: PVFs are more frequent compared to other types of PRF and are often associated to CD; surgical treatment has a risk of 50% recurrence. Repeat IPAA is the best surgical approach with a 42.1% recurrence rate.